2018
DOI: 10.1109/tevc.2017.2712906
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Bilevel Optimization: From Classical to Evolutionary Approaches and Applications

Abstract: Bilevel optimization is defined as a mathematical program, where an optimization problem contains another optimization problem as a constraint. These problems have received significant attention from the mathematical programming community. Only limited work exists on bilevel problems using evolutionary computation techniques; however, recently there has been an increasing interest due to the proliferation of practical applications and the potential of evolutionary algorithms in tackling these problems. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
315
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 681 publications
(318 citation statements)
references
References 181 publications
(199 reference statements)
0
315
0
3
Order By: Relevance
“…Level 2 optimizes the hourly dispatch of BESS and DR programs in order to maximize the operational benefits of DSO. To solve the complex bilevel optimization problem, any evolutionary algorithm can be used . From literature survey, it is observed that GA is the most widely used technique for optimization problem of DG planning .…”
Section: Proposed Bilevel Optimization Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Level 2 optimizes the hourly dispatch of BESS and DR programs in order to maximize the operational benefits of DSO. To solve the complex bilevel optimization problem, any evolutionary algorithm can be used . From literature survey, it is observed that GA is the most widely used technique for optimization problem of DG planning .…”
Section: Proposed Bilevel Optimization Methodologymentioning
confidence: 99%
“…To solve the complex bilevel optimization problem, any evolutionary algorithm can be used. 36 From literature survey, it is observed that GA is the most widely used technique for optimization problem of DG planning. 37 Therefore, in this paper, GA has been used to solve the optimization problem at both levels.…”
Section: Proposed Bilevel Optimization Methodologymentioning
confidence: 99%
“…In general, the problem of designing CNN architectures for a target dataset D = {D trn , D vld , D tst } can be viewed as a bi-level optimization problem [7]. It can be mathematically formulated as,…”
Section: Introductionmentioning
confidence: 99%
“…Mathematically, finding Nash equilibria of such Stackelberg games requires solving a bilevel optimization problem, which, in general cannot be undertaken analytically, [26], and numerical approaches are required. However, standard techniques are not able to deal with continuous and high dimensional decision spaces, as those appearing in AML applications.…”
Section: Introductionmentioning
confidence: 99%